Clinical and prognostic significance of left ventricular outflow tract velocity time integral (LVOT-VTI) in patients with chronic heart failure. (3rd October 2022) - Gentile, F; Buoncristiani, F; Chubuchny, V; Sciarrone, P; Panichella, G; Bazan, L; Gasperini, S; Fabiani, I; Taddei, C; Poggianti, E; Petersen, C; Pasanisi, E; et al.
Abstract: Background: The echocardiographic evaluation of cardiac output relies on the product of the flow across the left ventricular outflow tract (LVOT), estimated through its velocity time integral (LVOT-VTI), and its cross-sectional area, estimated through the formula πr2. Considering the geometrical assumption behind such formula, LVOT-VTI has been proposed as a more reproducible surrogate of cardiac systolic function and showed prognostic value in the critical care setting. However, the role of such measure in patients with chronic heart failure (HF) remains unexplored. Objective: To assess the clinical and prognostic significance of LVOT-VTI in a contemporary cohort of patients with chronic HF. Methods: Outpatients with chronic HF with a LV ejection fraction <50% were prospectively enrolled to undergo a clinical, echocardiographic, and biohumoral assessment, and were followed-up for the endpoint of all-cause death. Results: Finally, 971 patients were enrolled (71±12 years, 72% men, 50% ischemic etiology, LVEF 35±9%). Most patients showed a NYHA class I-II (74%) and were treated with ACE-inhibitors/ARBs or ARNI (81%), beta-blockers (95%), and mineralocorticoid receptor antagonists (71%). Patients were distinguished in three subgroups according to LVOT-VTI tertiles <19 (n=324), 19–24 (n=324), or ≥24 (n=323). Compared with the other two subgroups, patients with LVOT-VTI <19 showed worse NYHA class, lower LVEF and tricuspid annular plane systolic excursion (TAPSE), and higher E/e', left atrial volume index (LAVi), estimated systolic pulmonary arterial pressure (sPAP), and NT-proBNP concentration (all p<0.001). No differences were observed as for patients' age, HF etiology, and therapies (all p>0.05). Over a median follow-up of 22 (9–34) months, 103 (11%) patients met the primary endpoint. LVOT-VTI significantly stratified the risk of death, observing 65 (20%), 21 (7%), and 17 (5%) events across the subgroups with values <19, 19–24, or ≥24 (log-rank 33, p<0.001). At multivariable regression analysis, LVOT-VTI <19 (HR 2.06 [95% 1.21–3.49], p=0.008), but not LVEF <30% (p=0.614) was an independent predictor of all-cause death in a model adjusted for age, sex, ischemic etiology, renal function, hemoglobin, E/e', LAVi, TAPSE, sPAP, and NT-proBNP. Conclusion: LVOT-VTI is associated with disease severity and is a strong predictor of all-cause death in patients with chronic HF. Funding Acknowledgement: Type of funding sources: None.